The Effects of Rapamycin on the Intestinal Graft in a Rat Model of Cold Ischemia Perfusion and Preservation - Ibitamuno Caleb; Benedek Kasza; Luca Erlitz; Dávid Semjén; Péter Hardi; Lilla Makszin; Szilárd Rendeki; Ildikó Takács; Tibor Nagy; Gábor Jancsó (Metabolites, 2022)
Attenuating the rheological and structural consequences of intestinal ischemia-reperfusion-injury (IRI) is important in transplant proceedings. Preconditioning is an often-proposed remedy. This technique uses physical or pharmacological methods to manipulate key ischemia pathways, such as oxidation, inflammation, and autophagy, prior to ischemia. This study determined the time-dependent effects of Rapamycin preconditioning on small-bowel grafts undergoing cold ischemia perfusion and preservation. Our main parameters were mucosa and cell injury and autophagy. A total of 30 male Wistar rats were divided into 5 groups: sham, preservation-control, and 3 treated groups (Rapamycin administered either 0, 30, or 60 min prior to perfusion). After perfusion, the intestines were placed in chilled IGL-1 solution for 12 h. Thereafter, they were reperfused. Histology and bioanalysis (LDH and lactate) were used to ascertain intestinal injury while immunohistochemistry was used for measuring changes in autophagy markers (Beclin-1, LC3B, and p62 proteins). The results show no significant difference amongst the groups after vascular perfusion. However, intestinal injury findings and autophagy changes demonstrate that administering Rapamycin 30 min or 60 min prior was protective against adverse cold ischemia and reperfusion of the intestinal graft. These findings show that Rapamycin is protective against cold ischemia of the small intestine, especially when administered 30 min before the onset.